Bad Apples on Rotten Tomatoes: Critics, Crowds, and Gender Bias in Product Ratings - Luis Aguiar (CESifo GmbH, 2024)
Consumers considering the purchase of experience goods can rely on both critics and crowd-based evaluations to guide their decisions. Due to divergent incentives, however, critics and crowd assessments may incorporate different information. In the context of the movie industry, I investigate whether crowd reviewers provide gender-neutral product evaluations relative to professional critics. I classify movies as male or female based on the gender composition of their cast and estimate how the gender gap in movie rating scores differs across critics and crowds. Results show that while critics tend to assess both male and female movies similarly, the gender gap in ratings increases substantially under crowd-based ratings and at the expense of female movies. Notably, female movies receive a higher proportion of extreme low ratings, predominantly from male crowd reviewers. Using a rating design change implemented by the review-aggregating platform Rotten Tomatoes, results indicate that this overall increase in gender inequality is driven by a selected group of online reviewers rather than by a general bias against movies with more prominent female presence. These findings have important implications for the gate-keeping role of review-aggregating platforms in reducing bias against female representation in product ratings.
Keywords: D83; L15; L82; O33; 330; digital platforms; product ratings; critics; crowds; gender bias; movie industry